Acceleration, Deceleration and Stagnation of Agricultural Investments and Productivity in Nigeria (1981 – 2020) - Ifeanyi A. Maduike; Jude C. Nwaru; Onwuchekwa R. Iheke; Onyebuchi C. Korie; Igwe I. Ukoha; Chinasaokwu S. Onyemauwa (Bulgarian Journal of International Economics and Politics)
This study examines the acceleration, deceleration and stagnation of agricultural investments (public and private) and agricultural productivity in Nigeria. Data were obtained for the period 1981 to 2020 and analysed using exponential time series function and the quadratic time trend model. The obtained result showed that FDI growth rate for the period was 13.24%, public investment in agriculture (26.95%) and private sector investment in agriculture (20.32%), whereas, agricultural productivity declined by 0.78%. Further results showed that there was acceleration in growth of public and private sectors’ investment in agriculture while FDI in agriculture and agricultural productivity stagnated. It was concluded that increased investments in agriculture has not improved the productivity of agriculture in Nigeria. Therefore, investments should focus on agricultural technologies in order to maximize the yield per input.